2013
DOI: 10.1124/jpet.112.202036
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Its Analog 5-Methoxycarbonylamino-N-Acetyltryptamine Potentiate Adrenergic Receptor-Mediated Ocular Hypotensive Effects in Rabbits: Significance for Combination Therapy in Glaucoma

Abstract: Melatonin is currently considered a promising drug for glaucoma treatment because of its ocular hypotensive and neuroprotective effects. We have investigated the effect of melatonin and its analog 5-methoxycarbonylamino-N-acetyltryptamine, 5-MCA-NAT, on b 2 /a 2A -adrenergic receptor mRNA as well as protein expression in cultured rabbit nonpigmented ciliary epithelial cells. Quantitative polymerase chain reaction and immunocytochemical assays revealed a significant b 2 -adrenergic receptor downregulation as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
3
32
0
Order By: Relevance
“…Long-term effects of melatonin and 5-MCA-NAT have been described in the eye. These effects are mainly due to the modulation of carbonic anhydrase and regulation of adrenergic receptor gene expression (Crooke et al, 2011(Crooke et al, , 2012b(Crooke et al, , 2013. Altogether, we have demonstrated not only the acute and long-term effect of 5-MCA-NAT on IOP but also that 3-month treatment in a glaucoma situation helps ameliorate the elevation of IOP in our mouse model.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Long-term effects of melatonin and 5-MCA-NAT have been described in the eye. These effects are mainly due to the modulation of carbonic anhydrase and regulation of adrenergic receptor gene expression (Crooke et al, 2011(Crooke et al, , 2012b(Crooke et al, , 2013. Altogether, we have demonstrated not only the acute and long-term effect of 5-MCA-NAT on IOP but also that 3-month treatment in a glaucoma situation helps ameliorate the elevation of IOP in our mouse model.…”
supporting
confidence: 60%
“…This molecule and some of its analogs, such as 5-methoxycarbonylamino-N-acetyltryptamine (5-MCA-NAT), produce a marked reduction in IOP in normotensive and hypertensive conditions (Serle et al, 2004;Crooke et al, 2013;Martínez-Águila et al, 2013;Pescosolido et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This ocular hypotensive effect seems to be mediated by ciliary body receptors (MT 2 and an unidentified receptor classically named MT 3 ) and final inhibition of ciliary chloride secretion . Furthermore, melatonergic compounds provide a sustained reduction in IOP through regulation of ciliary genes expression and potentiate the hypotensive action of classic antiglaucomatous drugs such as timolol and brimonidine …”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 99%
“…In addition to its pleiotropic actions, melatonin possesses an advantage over other possible candidates due to its amphiphilic character, which enables it to enter any fluid, cell, or subcellular structures including mitochondria . Furthermore, Crooke and colleagues have demonstrated that the melatonin combination with classical antiglaucoma drugs potentiates their effects on animals . Therefore, the combination of melatonin with other drugs could improve the efficacy of classical drugs in patients with the mentioned diseases.…”
Section: Epilogue and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation